KEHIDUPAN ANAK PUNK DI KOTA PEKANBARU - Anggraini, Rini; Asriwandari, Hesti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Punk is a subculture that was born in London, England. Punk have axclusive identity in terms of appearance and behavior they display. The phenomenon of the spread of punk has become a problem for Pekanbaru city government.Punk kids always spoil beauty of the Pekanbaru city, punk kids who disturb traffic order or prickly punk troublemakers.This research was conducted at the traffic lightwhich became a punk kids doing activities that crossroads Tuanku Tambusai precisely at the intersection of Red Light Mall SKAPekanbaru(Subdistrict Tampan),Gramedia Corner(Subdistrict of Pekanbaru City), Pasar Pagi Arengka Corner(Subdistrict Marpoyan Damai) and Ramayana around the Market Kodim District(Pekanbaru City). This type of research is descriptive, the sampling technique used purposive sampling or the sample aiming so that informants on research 5 informants from 4 locations totaling 20 people. Data collection techniques with literature studies, field studiesnamely : observation, interview, questionnaire, documentation and study of the data online. These data are analyzed in terms of the child's identity and family background punk. Then the data compiled in the form of a single table after it sought the percentages described in detail.The results showed that the punks in town pekanbaru comes from a family economy weak so that the overall child punkers want to break away from their parents, ease the burden on parents and wants to be independent, punkers child is also not an original pekanbaru residents, predominantly immigrant population and can also be seen that the behavior of punk kids who are in town pekanbaru can be seen in terms of knowledge, attitudes and actions.In terms of their knowledge to understand and know the ideologies owned punk in general, the application of ideology can be seen in terms of looks and accessories that are used as well as activities such as singing does, gathered-together, drinking adulterated alcohol, sleeping in a doorway, free sex, walks out of the area, screen printing, tattoos and piercing. While the factors that encourage the existence of the punk community can be seen from the internal factors and external factors.Keyword : Child Punk, Activities, Deviation